ANALISA STRATEGI BERSAING PEMASARAN PRODUK PT POWER SUMBER SOLUSINDO - Ahmad Nurhadi; Dayat Hidayat; Edi Sukarjono (Universitas Pamulang, 2015)
COMPETITIVE ANALYSIS OF MARKETING STRATEGY POWER SUMBER SOLUSINDO, PT. This research aims to determine what marketing strategies that can be done at Power Sumber Solusindo, PT of marketing strategies that have been implemented by considering the factors of internal and external factors on the Company, and to improve the competitiveness in product marketing in corporate environments Oil and gas in Indonesia, resulting in maximum profit. The method used in this thesis is a descriptive research model, using analysis of internal factors, external and analysis through the SWOT analysis and the BCG matrix. BCG matrix method is used to determine the rate of market growth in Power Sumber Solusindo, PT and has targeted a growth of 11.85%, and market share has more than the ability to compete with competitors. The results of the SWOT analysis of Power Sumber Solusindo, PT yield that the right strategy at Power Sumber Solusindo, PT is to perform three steps namely the Strategic Growth Markets (Market Growth Strategy), Strategy Market Share (Market Share Startegy), Market Expansion Strategy (Expansion Strategy). This study concluded that the competing product marketing strategy that can be used is to make investments to Strengthen its dominant position in emerging markets, and deepen market penetration power that has mastered marketing to accelerate growth, as well as to make cooperation with the principal to get the product with ease competitive prices. Keywords: Competitive Strategy, Marketing, Product, Power Sumber Solusindo PT